HUBUNGAN KUALITAS TIDUR DAN KECEMASAN PADA PASIEN HIPERTENSI - Ayu, Diyona Permata; Fitri, Nurwijaya (JURNAL SMART ANKes, 2025)
Hypertension is a condition in which systolic blood pressure rises to ? 140 mmHg and diastolic blood pressure rises to ? 90 mmHg, as determined by at least two measurements taken five minutes apart while at rest. This study aims to analyze the relationship between sleep quality and anxiety in hypertensive patients at the Gerunggang Community Health Center in 2025. This study used a quantitative method with a correlational design and a cross-sectional approach. The study population consisted of all hypertensive patients who visited and sought treatment at the Gerunggang Community Health Center in Pangkalpinang in July 2025, totaling 260 people, with a sample of 80 respondents selected using random sampling techniques. The research instruments were a sleep quality questionnaire (PSQI) and a GAD7 anxiety questionnaire. Data analysis was performed using the chi-square test and the Pearson correlation test. The results showed a significant correlation between sleep quality and the incidence of hypertension with a p-value of 0.000. In addition, there was a significant correlation between anxiety and the incidence of hypertension with a p-value of 0.031. The direction of the correlation indicates that the poorer the sleep quality, the higher the anxiety level tends to be. The conclusion of this study is that there is a significant correlation between sleep quality and anxiety in hypertensive patients at the Gerunggang Community Health Center in 2025. It is hoped that health workers can improve education about healthy sleep patterns and anxiety management as part of efforts to control hypertension in primary health care services. Keywords: Hypertension, Sleep Quality, Anxiety